A Parallel Algorithm for Detecting Complexes in Protein-protein Interaction Networks with MapReduce (Journal of Fiber Bioengineering and Informatics, 2015)
Detecting protein complexes from Protein-protein Interaction (PPI) networks has been the focus of manyrecent efforts on protein. With the appearance of big data and large scale PPI networks, traditionalsequential methods, which analyze interaction networks and detect protein complexes, do not utilize highperformance computing. In this paper, we propose a parallel algorithm using cloud computing method toimprove the computational efficiency and detect protein complexes. Because MapReduce programmingmodel simplifies the implementation of many data parallel applications, firstly we use it to calculate thevalue of each edge and the value of each node from PPI networks, then expand complexes. At last, weperform the algorithm on different data to test the speedup of the algorithm. Moreover, through theparallel algorithm is compared with sequential method, experimental results show that the running timeof parallel algorithm is short. We get a conclusion that parallel algorithm can also accurately assignproteins with similar functions to a complex.
Keywords: PPI Network; Protein Complexes; Parallel Algorithm; MapReduce